Halogen Bonding Increases the Potency and Isozyme Selectivity of Protein Arginine Deiminase 1 Inhibitors. Issue 36 (1st August 2019) - Mondal, Santanu; Gong, Xuefeng; Zhang, Xiaoqian; Salinger, Ari J.; Zheng, Li; Sen, Sudeshna; Weerapana, Eranthie; Zhang, Xuesen; Thompson, Paul R.
Abstract: Protein arginine deiminases (PADs) hydrolyze the side chain of arginine to form citrulline. Aberrant PAD activity is associated with rheumatoid arthritis, multiple sclerosis, lupus, and certain cancers. These pathologies established the PADs as therapeutic targets and multiple PAD inhibitors are known. Herein, we describe the first highly potent PAD1‐selective inhibitors (1 and 19 ). Detailed structure–activity relationships indicate that their potency and selectivity is due to the formation of a halogen bond with PAD1. Importantly, these inhibitors inhibit histone H3 citrullination in HEK293TPAD1 cells and mouse zygotes with excellent potency. Based on this scaffold, we also developed a PAD1‐selective activity‐based probe that shows remarkable cellular efficacy and proteome selectivity. Based on their potency and selectivity we expect that 1 and 19 will be widely used chemical tools to understand PAD1 biology. Abstract : The iodine‐dependent increase in potency and isozyme selectivity of protein arginine deiminase 1 (PAD1) inhibitors is discussed. Iodine atoms form a halogen bond with PAD1. Because of high lipophilicity of iodine, these inhibitors exhibit excellent cellular activity. Using this scaffold, a PAD1‐selective chemical probe was developed with superior cellular efficacy.